Epicardial obesity as a significant preclinical predictor of atherosclerosis of brachiocephalic arteries. (25th November 2020) - Ott, A; Chumakova, G.A
Abstract: : Obesity is one of the significant factors of cardiovascular risk. Nowadays it is understood that it is visceral obesity (VO), which has metabolic activity due to the synthesis of adipokines, that determines cardiometabolic risk. The effect of epicardial obesity (EO), as a variant of VO on the formation of cardiometabolic risk (in particular coronary atherosclerosis) is being actively studied. The role of EO in the development of atherosclerosis of other localizations has been little studied. Objective: To study the predictor value of EO as well as traditional criteria for obesity: body mass index (BMI) and waist circumference (WC) for the formation of atherosclerosis of brachiocephalic arteries (BCA). Materials and methods: The study included 140 men 45.2±4.3 years old with arterial hypertension (AH) of the 1–3 degree and the absence of clinical manifestations and anamnesis of atherosclerosis of any localizations with a BMI of 20–35 kg /m 2 and abdominal obesity according to WC ≥94 cm. Patients were divided into two groups depending on the thickness of the epicardial adipose tissue (EAT) measured behind the free wall of the right ventricle by echocardiography. Group 1 consisted of 60 patients with epicardial obesity (EAT ≥7 mm), group 2 included patients without epicardial obesity (EAT <7 mm). Subclinical atherosclerosis of BCA was evaluated in all subjects using duplex brachiocephalic arteries (BCA). Results: When assessing the thickness of the intima-media of the carotid arteries (TIM), a subclinical marker of BCA atherosclerosis, higher average TIM values in group 1 (EAT ≥7 mm) were revealed (1.09±0.34 mm versus 0.74±0, 05 mm in group 2 (EAT <7 mm) (p=0.0001). Prevalence of subclinical BCA atherosclerosis from (20–45%) in group 1 patients was found in 57%, in group 2 only 4% (p=0.01). In the first group, hemodynamically significant asymptomatic BCA stenosis (50–65%) was found in 8% of patients. No hemodynamically significant BCA stenosis was detected in the second group. Using ROC analysis, the threshold value of EAT (9.25 mm) was obtained as a risk factor for hemodynamically significant stenoses of BCA (50% or more) with high prognostic significance (the area under the curve was 0.92). Using multivariate analysis of variance, the effect of various criteria of obesity on the formation of BCA atherosclerosis was studied. As a result of the analysis it was revealed that only EAT (p=0.02) influenced the development of BCA atherosclerosis (TIM more than 1.3 mm). WC and BMI did not affect the development of BCA subclinical atherosclerosis (p=0.21; p=0.24, respectively). Conclusions: EO (EAT ≥7 mm) is an early marker of BCA subclinical atherosclerosis in contrast to the traditional criteria for obesity (BMI, WC). Patients with EAT of 9.25 mm or more need additional examinations and the appointment of pharmacotherapy aimed at the prevention of secondary complications. Funding Acknowledgement: Type of funding source: None